2002
DOI: 10.1007/bf02897976
|View full text |Cite
|
Sign up to set email alerts
|

Relation between cotinine in the urine and indices based on self-declared smoking habits

Abstract: The rate of misclassification in this study was considered to be comparatively low. Several studies have also assessed the reliability of the questionnaire on smoking habits, and found different misclassification rates, indicating the dependence on the race and number of subjects tested. To our knowledge, there were only a few surveys on smoking among large groups, particularly in Japan, such as this one, therefore the results obtained in this study are meaningful.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…We found that deep inhalation increased risk of lung cancer although the odds ratios were no longer significant after adjusting for the CSI. This result should be seen with caution, since self-reporting of inhalation patterns may not adequately reflect cotinine levels [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…We found that deep inhalation increased risk of lung cancer although the odds ratios were no longer significant after adjusting for the CSI. This result should be seen with caution, since self-reporting of inhalation patterns may not adequately reflect cotinine levels [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…We are currently involved in a separate project to review accuracy of reporting smoking habits, using cotinine to validate self-reported smoking habits. We are aware of five studies in Asian populations, three in Japan 62– 64 , one in Korea 65 and one of South-East Asians resident in the USA 66 , which report results separately for never, ex and current smokers and by sex. All five give results for women, and four do so for men, and the proportion of true current smokers in self-reported never or ex-smokers (as judged by high cotinine levels) in women (range 12.3% to 61.6%, overall 45.8%) is much higher than it is men (range 0.4% to 6.0%, overall 3.4%).…”
Section: Discussionmentioning
confidence: 99%
“…Trained personnel obtained the following information at the time of recruitment and at each visit thereafter: age, sex, spirometric values, mMRC dyspnea scale, six minute walk distance (6MWD), and the body mass index (BMI), calculated as the weight in kilograms divided by height in meters 2 . Patients were asked about their smoking history (age at initiation and discontinuation, as well as intensity), and if they still smoked (current or former) [ 10 ]. From this information we calculated the total smoking exposure and expressed it as pack-years.…”
Section: Methodsmentioning
confidence: 99%